Analisis Pengaruh Pengembangan Karir dan Beban Kerja Terhadap Prestasi Kerja Karyawan Pada PT. Vilo Gelato - Yohanes Sugiyanta; Umar Usman (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2023)
At PT Vilo Gelato, it is suspected that there is a decrease in employee career development due to no promotion, while the workload is due to noise when using machines, and work performance is due to a lack of discipline. The purpose of this study was to examine how much influence career development and workload variables have on employee performance at PT. Vilo Gelato. In addition, leaders must also pay attention to their employees, by providing encouragement or motivation. The purpose of this study is to determine whether there is an influence or how much influence career development variables and workload have on employee performance at PT. Vilo Gelato. The purpose of this study is to examine how much influence career development variables and workload have on employee performance at PT. Vilo Gelato. This study used quantitative methods. Data collection techniques by giving questionnaires to respondents and interviews with related parties. The number of samples in this study was 50 respondents. The respondents are employees of PT. Vilo Gelato production parts. This sample determination uses the Solvin formula for 10% of the population of 100 employees. In proving and analyzing this, a simple linear regression test method for career development on employee work performance is used, namely Y = 13,134 + 0.660, and simple linear regression of workload to employee performance is Y = 8,815 + 0.776. So, for the multiple linear regression method, Y = 7.626 + 0.396X1 + 0.420X2. The results of data processing using SPSS version 26 found that Rsquare was 65.5%. This means that career development variables and workload can explain employee performance variables by 65.5%. The rest were influenced by other variables that were not used in the study. From the results of this study concluded that partially seen from the results of analysis on the t-count test (X1), which was 3,521 and 0.001 sig. Therefore, H0 is rejected and Ha is accepted, which means that career development has a positive and significant influence on employee performance at PT. Vilo Gelato. Judging from the results of the t-test analysis, the count (X2) is 3,118 and the sig is 0.003. Therefore, H0 is rejected and Ha is accepted, which means that the workload has a positive and significant influence on employee performance at PT. Vilo Gelato. simultaneously it can be proven by the calculated F test value of 44,530 and the F table of 3.20 with a sig below 0.000. In this case career development and workload has a positive and significant effect on employee performance at PT. Vilo Gelato.